Concise Synthesis and Fertility-Promoting Activity of Thiamidol - ZHU Rouyu; GUO Lina; ZHU Jun; DIAO Hua; SHAO Zhiyu (东华大学学报（英文版）, 2023)
O69; In order to make the synthetic route of Thiamidol more efficient and easier to scale up,a new method was developed.The compound 2,4-dihydroxyacetophenone was dissolved in ethyl acetate and brominated with cupric bromide.After bromination,the mixture was filtered to remove cuprous bromide.The obtained ethyl acetate solution containing 2-bromo-1-(2,4-dihydroxyphenyl)ethanone was directly reacted with(2-methylpropanoyl)thiourea to obtain the precipitate of Thiamidol hydrobromide.The precipitate was neutralized by deacidification and recrystallized to afford Thiamidol with high purity.In addition,in the screening of fertility-promoting substances,Thiamidol was found to be effective in protecting human sperm from motility loss in vitro.This suggests that it may have potential application in fertility protection and promotion.